2009
DOI: 10.1111/j.1365-2915.2009.00835.x
|View full text |Cite
|
Sign up to set email alerts
|

A simple, heat‐sterilizable artificial diet excluding animal‐derived ingredients for adult blowfly, Lucilia sericata

Abstract: Artificial diets have been developed for Lucilia sericata (Meigen) blowfly larvae; however, diets for adults have not yet been developed. An adult diet that excludes animal tissues and animal-derived ingredients and promotes not only ovarian development, but also oviposition, would aid in basic research and maggot debridement therapy. We have successfully developed artificial diets that exclude animal tissues and animal-derived ingredients for L. sericata adults. The outcomes of the diets were comparable with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 30 publications
1
8
0
1
Order By: Relevance
“…The vertical life table did not reveal significant differences regarding mortality and survival parameters concerning the diets evaluated here. On the one hand, the study by Zhang et al [33] showed that the E-PM diet induced higher survival rates, similar to those observed here for the LI instar, puparia and adult stages. On the other hand, during the development of S. magellanica under laboratory conditions it was observed that the survival rate varied according to developmental stage, for example, being low in puparia, which could have been related to the morphological and physiological disorganisation produced during metamorphosis [34].…”
Section: Discussionsupporting
confidence: 90%
“…The vertical life table did not reveal significant differences regarding mortality and survival parameters concerning the diets evaluated here. On the one hand, the study by Zhang et al [33] showed that the E-PM diet induced higher survival rates, similar to those observed here for the LI instar, puparia and adult stages. On the other hand, during the development of S. magellanica under laboratory conditions it was observed that the survival rate varied according to developmental stage, for example, being low in puparia, which could have been related to the morphological and physiological disorganisation produced during metamorphosis [34].…”
Section: Discussionsupporting
confidence: 90%
“…Research has focused on the refinement of rearing techniques. For example, in recent years, noteworthy effort has been made in the testing of new fly species for MT in addition to the widely used L. sericata and L. cuprina (Dallavecchia et al ., ; Masiero et al ., ; Díaz‐Roa et al ., ), the development of artificial diets for both adult and larval flies (Tachibana & Numata, ; Zhang et al ., ), the development of efficacy assays for medicinal maggots (Blake et al ., ; Čičková et al ., ; Wilson et al ., ; Pickles & Pritchard, ), the potential for sterile rearing of flies from egg to adult (Gasz & Harvey, ), and the development of transgenic L. sericata to enhance MT wound healing properties (Linger et al ., ). However, although there is much information on the rearing of L. sericata and other calliphorid flies that comes from the forensic and other entomological literature, there is considerable variation in rearing set‐ups and conditions depending on the nature of the study, species of fly and field of research.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, the literature to date has focused on isolated discussions of specific issues such as diet improvement and sterilization protocols in the production process (e.g. Zhang et al ., ; Thyssen et al ., ; Blystone & Hansen, ; Limsopatham et al ., ), or the relative effectiveness of medicinal maggot application methods in the treatment echelon (e.g. Steenvoorde et al ., ; Čičková et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…El colesterol es el principal esterol encontrado en los insectos, que sirve como un componente estructural de las membranas celulares y actúa como precursor de ecdisteroides, siendo fundamental en el desarrollo normal de la mayoría de los insectos (Zhang et al 2009), por lo tanto, la efectividad de la dieta LP, se debe a que es considerada como una fuente rica en colesterol. También, otros estudios han demostrado que la dieta LP es una de las más manipuladas para el desarrollo de los insectos, debido a su composición en dos importantes proteínas: caseina y lactoalbumina (Loureiro et al 2005).…”
Section: Resultados Y Discusiónunclassified